IMPLEMENTASI BIMBINGAN ROHANI ISLAM DALAM MEMOTIVASI KESEMBUHAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH (RSUD) SINJAI - Surianti, Surianti (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2024)
The implementation of Islamic Spiritual Guidance is the process of sustaining and maintaining the patient's spiritual activities in order to gain the sincerity, patience or calmness as well as motivation to heal despite the disease. Patients who are in pain physically must also exhibit mental disorder, such as anxiety, uneasiness and depression. This research attempted to ascertain the ways in which Islamic spiritual guidance was implemented to encourage inpatients' recovery, as well as the aspects of Islamic spiritual guidance that either facilitate or impede inpatients' recovery at Sinjai Regional General Hospital. This research is a qualitative study and the data was gathered through observation, interviews and documentation. In this study, the implementation of Islamic spiritual guidance at RSUD Sinjai is very necessary in providing guidance to the patients, especially for daily inpatients through approached to patients or in person interaction. The patients can received guidance from doctors and nurses on how to continue worshiping, receiving guidance, and praying for the patients recovery. The Islamic spiritual guidance comes in two forms, there are psychological guidance that comes from patience and honesty, and spiritual direction that comes from faith, prayer, dhikr, and prayer. The supporting factors is the patients who can be open minded, the personality of doctors and nurses, acceptance from patients and patients' families and the support from families. While the inhibiting factors are patients who are not open minded, the patient's language and Islamic spiritual counselors.